Coexistence of particularity in the universality of musical sensation - Jatmika, Ovan Bagus (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
This research is motivated by the debate about the issue of the universality of music. The question to be answered is, at what level does this aspect of musical universality emerge? This question is asked because, at a material level, it is clear that every piece of music is different and cannot be said to be the same, but at the same time, people tend to be able to enjoy music even if they don’t know the type or language of the music they are listening to, intuitively, unlike verbal language. Efforts to answer these questions bring this research under the qualitative umbrella with a phenomenological approach. In the context of this research, the issue of music is examined through the experience of musical sensations and reviewed using Deleuze’s theory of sensation. Data on musical sensation experiences was collected by conducting semi-structured interviews with five musicians from different genres, namely classical, jazz, pop, experimental and traditional. The research results show that the universality aspect of music is at the level of sensation, not sound material. In this case, sensation is only possible through empirical experience when people intensifically encounter sound material. This also shows that the term musical universality is not merely a metaphorical expression, but rather explains the existence of a coexistence relationship between musical material and sensation. So this finding can contribute to the need for the musician to think about performance strategies if they want to produce a universal sensation experience.